PENGARUH MODEL PEMBELAJARAN TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA PADA MATERI BANGUN RUANG SISI DATAR - Sambuaga, Telly; Emor, Jorie; lakoro, cindrianty (Universitas Negeri Manado, 2020)
ABSTRACT. This study was conducted to determine the effect of think pair share learning models on student learning outcomes on the material on flat side spaces. This study uses a posttest only control design. The subjects of this research are students of class VIII B as an experimental class consisting of 24 students and students of class VIII A as a control class consisting of 23 students in SMP Negeri 2 Tondano. The data obtained are the results of the Posttest in the experimental class and the control class. With an average of 81.58 experimental class learning outcomes and an average of 80.30 control class learning outcomes. Normality test data is fulfilled with normally distributed data. The results of data analysis with a real level of 0.05 obtained t_count = 2.912702> t_table = 1.67943. Based on these results it can be concluded that student learning outcomes using think pair share models on the material of flat side space are higher than the learning outcomes of students who use conventional learning Â Keywords: conventional, flat plane shapes, Think Pair Share